Inhibitory neuronal changes following a mixed diffuse‐focal model of traumatic brain injury. Issue 2 (8th August 2019) - Carron, Simone F.; Sun, Mujun; Shultz, Sandy R.; Rajan, Ramesh
Abstract: Traumatic brain injury (TBI) can result in excitation: inhibition imbalance, as well as a range of chronic neurological deficits. However, how TBI affects different interneurons, and how this relates to behavioral abnormalities, remains poorly understood. This study examined the effects of a mixed diffuse‐focal model of TBI, the lateral fluid percussion injury (LFPI), on interneurons, 8 weeks post‐TBI in rats. Brains were labeled with antibodies against calbindin, parvalbumin, calretinin, neuropeptide Y, and somatostatin, and the number of interneurons were assessed in the cortex and hippocampus following LFPI. LFPI caused a reduction in the numbers of interneurons mediating both perisomatic and dendritic inhibition in the somatosensory cortex. In hippocampus, there were heterogenous changes in the number of interneurons while motor cortex, showed no obvious loss in any of the subsets of interneurons after TBI. In parallel to the investigations of changes in the number of interneurons, we also investigated the long‐term behavioral consequences of LFPI. Behaviorally, rats given an LFPI displayed transient reduction in performance in motor tasks and were significantly impaired in reversal learning in the water maze task post‐TBI. We also report here progressive neurodegeneration in cortex and hippocampus indicated by Fluoro‐Jade C in the different brain areas examined after injury. Our findings suggest differential vulnerability of inhibitory neurons to LFPI in the different brain areas examined after injury. These data will aid in evaluation of new treatments for TBI and help target specific neuronal subtypes as a function of injury time and type. Abstract : Using immunohistochemistry and Fluoro‐Jade C, authors show differential vulnerability of inhibitory neurons and progressive neurodegeneration in cortex and hippocampus following lateral fluid percussion injury (LFPI). This figure shows Fluoro‐Jade C stained degenerating neurons in the CA2/3 and dentate gyrus of LFPI animals.